THE EPENTHETIC VOWEL QUALITY IN DAGBANI LOANS: A FEATURE GEOMETRY ACCOUNT (Bucharest Working Papers in Linguistics, 2025)
This paper explores the epenthetic vowel quality in Dagbani loanwords adapted from English and Arabic within the Feature Geometry (FG) model of Clements & Hume (1995). The findings reveal that vowel epenthesis plays a pivotal role as a syllable repair strategy in Dagbani. Three distinct strategies, namely vowel harmony, local/consonantal assimilation, and default vowel epenthesis, were identified to account for the quality of epenthetic vowels in Dagbani loanwords. Default vowel insertion emerged as the primary strategy, with the insertion of the central high vowel /ɨ/ and the front high vowel /i/. Vowel harmony was employed when the intervening consonant was a liquid or dorsal, occurring in word-initial, word-medial, and word-final positions. Conversely, the consonantal assimilation strategy was applied primarily in word-final position. In the context of vowel harmony, only labial features were observed to harmonize, while the consonantal assimilation strategy entailed the spreading of both coronal (palato-alveolar) and labial features. Finally, a segmental representation is provided of the Dagbani place feature in borrowed words, in which both left-to-right and right-to-left feature spreading are attested